Social Media Use by Students in Colleges of Science in Two Selected Private Universities in Southwest, Nigeria - Fasae, Joseph Kehinde; Adegbilero-Iwari, Idowu (MiddleBelt Journal of Library and Information Science, 2015)
The paper investigates the use of social media for academic practices by science students in selected private universities in Southwest, Nigeria. The study is descriptive design and the population of the study is 505. Purposive sampling technique was employed while 80 copies of questionnaire distributed to the respondents were returned giving 100% return rate. Data collected was analysed using descriptive statistics. The results show that nearly all the science students use social media especially Facebook (96.50%) followed by Google+ (73.75%) and YouTube have (60.00%). Most of the students use it on daily basis to maintain existing relationship and to stay in touch with those that they rarely see in person. Receiving of unwanted messages and pictures (60.00%) together with distracted attention from main classroom activities (46.25%) were the major negative impacts of social media on the science students. The findings also revealed that the science students are knowledgeable in the use of social media while Google+ (78.75%) happened to be the most beneficial social media network. The study reveals challenges faced in the use of the social media while recommendations were made to provide adequate measure and improved the use of social media application by entire students in Nigeria and beyond.